1992
DOI: 10.4269/ajtmh.1992.47.709
|View full text |Cite
|
Sign up to set email alerts
|

A Model of the Transmission of Dengue Fever with an Evaluation of the Impact of Ultra-Low Volume (ULV) Insecticide Applications on Dengue Epidemics

Abstract: We have developed a deterministic susceptible, exposed, infectious, resistant or removed (SEIR) model of dengue fever transmission that enables us to explore the behavior of an epidemic, and to experiment with vector control practices. Populations of both host and vector are divided into compartments representing disease status (susceptible, exposed, infectious, and, for humans, resistant), and the flow between compartments is described by differential equations. Examination of the equilibrium points leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
167
1
12

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(190 citation statements)
references
References 0 publications
10
167
1
12
Order By: Relevance
“…3). The number of dengue cases does not increase at the beginning of the high-temperature period in the city (May and June); however, previous studies have reported that dengue epidemics take several months to reach a level where they can be recognized as the result of previous conditions (Guzman et al, 2000;Newton et al, 1992). Our results indicated that an extensive reduction in and the management of Ae.…”
Section: Discussioncontrasting
confidence: 59%
“…3). The number of dengue cases does not increase at the beginning of the high-temperature period in the city (May and June); however, previous studies have reported that dengue epidemics take several months to reach a level where they can be recognized as the result of previous conditions (Guzman et al, 2000;Newton et al, 1992). Our results indicated that an extensive reduction in and the management of Ae.…”
Section: Discussioncontrasting
confidence: 59%
“…In fact, it could be argued that insect outbreaks have underpinned the wider ecological discussion on whether populations undergo density dependent-regulation (Chaves & Koenraadt 2010;Nicholson 1958). In the applied context of disease control, vector outbreaks are of major importance given density-dependence implications for different control measures, such as larviciding (Agudelo-Silva & Spielman 1984;Wilson et al 1990), insecticide spraying (Newton & Reiter 1992;Oki et al 2011), and more recently, the field release of genetically modified mosquitoes (Legros et al 2009;Magori et al 2009). …”
Section: Hot Environments and Mosquito Outbreaksmentioning
confidence: 99%
“…Prevention and control of dengue and DHF currently depends on controlling the mosquito vector, A. aegypti, in and around the home, where most transmission occurs. Space sprays with insecticides to kill adult mosquitoes are not usually effective (38,107,115) unless they are used indoors. The most effective way to control the mosquitoes that transmit dengue is larval source reduction, i.e., elimination or cleaning of water-holding containers that serve as the larval habitats for A. aegypti in the domestic environment (38,115,137).…”
Section: Disease Prevention Programsmentioning
confidence: 99%